2012
DOI: 10.1111/bjdp.12004
|View full text |Cite
|
Sign up to set email alerts
|

The organization of attention in typical development: A new preschool attention test battery

Abstract: This article introduces a new battery of attention tests for typically developing and atypically developing children with a mental age of 3-6 years. In the light of adult and child studies supporting a model of distinct networks for specific attentional operations, tests in the current battery were selected with the aim of measuring functions of selective attention, sustained attention and attentional control (executive function). Normative data were collected from 154 typically developing children aged 3-6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 51 publications
7
64
0
Order By: Relevance
“…These findings indicate that interventions such as cognitive training need to be guided by research in order to ensure they are tailored to the individual needs of those with ID. For instance recent work into the development of attention in young TD children (3 to 4.5 years) has demonstrated that a two factor model of attention (sustained attention & selection and response) is more appropriate at this early stage in development (Breckenridge, Braddick & Atkinson, 2013b). This is particularly relevant for children with ID, whose cognitive functions are likely to be more in line with younger TD children than their chronologically age matched peers.…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 99%
“…These findings indicate that interventions such as cognitive training need to be guided by research in order to ensure they are tailored to the individual needs of those with ID. For instance recent work into the development of attention in young TD children (3 to 4.5 years) has demonstrated that a two factor model of attention (sustained attention & selection and response) is more appropriate at this early stage in development (Breckenridge, Braddick & Atkinson, 2013b). This is particularly relevant for children with ID, whose cognitive functions are likely to be more in line with younger TD children than their chronologically age matched peers.…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 99%
“…The internal reliability for each factor was estimated with Cronbach's Alpha coefficient. The tests included in the factor analysis were selected from theoretical premises from the most recent studies on this topic [57,59].…”
Section: Resultsmentioning
confidence: 99%
“…Manly et al [58] also suggested a three-factor model of sustained and selective attention and a higher-level "executive" attention, even in 6-to 16-yearold children. In younger children (under 4 years) [59] a two-factor model seemed to best capture attentional constructs. A two-factor model in younger children (3-to 6-year-olds) was also confirmed by Steele et al [57].…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor analytic studies have found attention to be a distinct factor among EF measures and to have a different developmental course then other EF abilities (Klenberg et al 2001). There is also evidence for differentiated components within a specific attention factor (Breckenridge et al 2013). Supporting the role of attention are studies demonstrating improvements in sustained attention between the ages of 3 and 5 that correspond to changes in EF (Corkum et al 1995;Mahone et al 2001).…”
Section: Introductionmentioning
confidence: 99%